Getting copyright right. - Cherry, S.M (IEEE spectrum)
Mandatory copyright licensing legitimized the early radio and cable TV industries. The article discusses if it can it do the same for the Internet. One answer to the copyright issues of digital music, which might also legitimize exchange services like Napster, is for Congress to order some form of compulsory or blanket licensing for downloaded music